Pemanfaatan Agama Bagi Anak-Anak Melalui Gerakan “Maghrib Mengaji” di Desa Hamparan Perak, Kabupaten Deli Serdang - Rabiatul Hawawa Rabiatul Hawawa Rabiatul Hawawa; Nirwana Anas (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The selection of Religion and Social-based Real Work Lectures (KKN) more specifically, namely the Koran action subsequent to playing out the Maghrib supplication in Hamparan Perak Town, Shop Serdang Rule is one of the endeavors to work with kids in learning the Koran which so far has not been accessible. The strategy utilized in the execution of this Social-based genuine work addresses is resource based local area improvement (ABCD) where the local area is the entertainer and determinant of advancement endeavors in the climate or frequently alluded to as local area driven improvement (CDD). As well as being a spot or office for learning the Koran, this action is supposed to proceed with even after the Genuine Work Talk period is over so kids have better Koran abilities. The positive effect of this